Analisis Sektor Basis dan Pertumbuhan Sektoral Kota Tangerang - Safira Amora; Dini Yuniarti; Agus Salim (Jurnal Simki Economic, 2022)
Regional development is one of few factors of national development. Regional economic growth leads to regional development. This study intends to determine whether regional potency has a substantial impact on Tangerang City's economic growth from 2015 to 2019. The research methods employed in this study are as follows: Location Quotient (LQ), Dynamic Location Quotient (DLQ), and analyzing the leading, prospective and mainstay sectors in the future. Based on the results of this study, potential sectors in Tangerang City are manufacturing industries, transportation and logistics, and the company services sector. Two of three potential sectors are supported by RPJMD of Tangerang City, are manufacturing industries, transportations, and the logistics sector